Synergistic Combination of Reductive Covalent Functionalization and Atomic Layer Deposition—Towards Spatially Defined Graphene-Organic-Inorganic Heterostructures - Liu, Xin; Yang, Bowen; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Angewandte Chemie International Edition, 2023)
Three-dimensionally (3D) well-ordered and highly integrated graphene hybrid architectures are considered to be next-generation multifunctional graphene materials but still remain elusive. Here, we report the first realization of unprecedented 3D-patterned graphene nano-ensembles composed of a graphene monolayer, a tailor-made structured organophenyl layer, and three metal oxide films, providing the first example of such a hybrid nano-architecture. These spatially resolved and hierarchically structured quinary hybrids are generated via a two-dimensional (2D)-functionalization-mediated atomic layer deposition growth process, involving an initial lateral molecular programming of the graphene lattice via lithography-assisted 2D functionalization and a subsequent stepwise molecular assembly in these regions in the z-direction. Our breakthrough lays the foundation for the construction of emerging 3D-patterned graphene heterostructures.
CRIS-Team Scopus Importer:2023-10-27
Keywords: 3D Patterning; Atomic Layer Deposition; Graphene Chemistry; Heteroarchitectures; Molecular Assembly